Where, when, how and what seagrass to transplant for long lasting results in transitional water systems: the cases of Cymodocea nodosa, Zostera marina, Zostera noltei and Ruppia cirrhosa - Sfriso, Andrea Augusto; Sciuto, Katia; Mistri, Michele; Munari, Cristina; Juhmani, Abdul-Salam; Buosi, Alessandro; Tomio, Yari; Sfriso, Adriano (Frontiers in Marine Science, 2023)
Seagrasses play a vital role in marine ecosystems worldwide. However, until recently these ecosystems were experiencing declines due to various global and local threats. In response to this issue, initiatives have been launched to combat seagrass loss by addressing local and regional major stressors and actively engaging in restoration efforts by transplantation. Although seagrass restoration has progressed significantly with the development of numerous transplant techniques, these are not always crowned with success. This is often due to the fact that the environmental parameters of water, sediment and biota of the recipient sites are not carefully considered in their suitability for transplantation. In this study, the multi-year experiences and data from numerous environmental surveys in transitional water systems have been condensed to define limit values for the ideal growth conditions and the extreme values in which the survival of four aquatic angiosperm species is possible: Cymodocea nodosa, Zostera marina, Zostera noltei and Ruppia cirrhosa.Approaches to transplants, seasonality and critical issues have been explored. The identified limits and parameters of water, sediment and biota will help to define the suitability of a recipient site for the rooting of seagrasses, increasing the chances of success for transplant operations.